KOLEKTIVITAS SEBAGAI SISTEM NILAI PANCASILA DALAM PERKEMBANGAN LINGKUNGAN STRATEGIS DI INDONESIA: SUATU STUDI REFLEKTIF - Hayatul Khairul Rahmat; M. Adnan Madjid; Syahti Pernanda (Universitas Sriwijaya, 2020)
Abstract: Respondin to the development of the strategic environment provides opportunities and motivation for efforts to solidify the values of Pancasila as a philosophy of national life. For this reason, the study is needed to understand the collectivity as a Pancasila value system in the development of the strategic environment in Indonesia. This research used a library research method with a descriptive approach. The findings of this research are the collectivity in the life of the Indonesian people is a form of joint work of the Indonesian people in achieving the common goals of the Indonesian people so that Indonesia continues to stand on the basis of Unity in Diversity (Bhinneka Tunggal Ika) and not on the basis of the minorities of Indonesia's diversity. Pancasila is a philosophy of the personality of the Indonesian nation that was born from the collectivity of the nation's culture so that becoming a Pancasila is certainly able to face the development of a strategic environment both at the national and local levels. The use of Pancasila has become an instrument in order to maintain the integrity of the Indonesia and also to support national security.Keywords: Pancasila, Strategic Environment, Collectivity. Abstrak: Menyikapi perkembangan lingkungan strategis memberikan peluang dan motivasi bagi upaya-upaya memantapkan nilai-nilai Pancasila sebagai falsafah hidup bangsa. Untuk itu, maka sangatlah diperlukan sebuah kajian untuk memahami tentang kolektivitas sebagai sistem nilai Pancasila dalam perkembangan lingkungan strategis di Indonesia. Penulisan ini menggunakan metode penelitian kepustakaan dengan pendekatan deskriptif. Temuan dari penelitian ini yaitu kolektivitas dalam kehidupan bangsa Indonesia adalah bentuk kerja bersama bangsa Indonesia dalam mencapai tujuan bersama bangsa Indonesia sehingga Indonesia terus berdiri atas dasar ke-Bhinneka Tunggal Ika dan bukan atas dasar minoritas-mayoritas dari keberagaman Indonesia tersebut. Pancasila merupakan sebuah falsafah kepribadian bangsa Indonesia yang terlahir dari kolektivitas budaya bangsa sehingga menjadi Pancasila tentunya mampu menghadapi perkembangan lingkungan strategis baik dalam tataran nasional maupun tataran lokal. Penggunaan Pancasila ini menjadi instrumen dalam rangka menjaga keutuhan Negara Kesatuan Republik Indonesia (NKRI) dan juga untuk mendukung keamanan nasional.Kata kunci: Pancasila, Lingkungan Strategis, Kolektivitias